Effective degradation of refractory nitrobenzene in water by the natural 4-hydroxycoumarin under solar illumination. (January 2019) - Wei, Tuo; Waqas, Muhammad; Xiao, Ke; Yang, Bo; Luo, Yu; Luo, Qiuhan; Zhang, Junmin; Wang, Mingliang; Zhu, Caizhen; He, Tingchao; Lu, Zhouguang
Abstract: In this study, nitrobenzene (NB) as typical refractory organic pollutants was effectively degraded by a new green approach, which was achieved by the chemical effect of natural organic matters (NOMs) under solar illumination as a potential natural degradation process. 4-hydroxycoumarin (4HC), which is natural compound and can be extracted from many plants, was found as an efficient photosensitizer to promote the photoreduction of NB to 4-aminophenol under the solar illumination. The reaction products were definitely identified by LC-MS/MS and 1 H NMR. The response spectrum of 4HC excited state (4H-chromene-2, 4-diol radical, S1 ) as key intermediate was also obtained by transient absorption spectroscopy (TAS) measurements, which showed that the decay time of S1 was around 250 ps. Then, the measurements of electron paramagnetic resonance (EPR) confirmed the existence of OH. As a result, the reaction mechanism between 4HC and NB was proposed. In addition, the influence parameters such as light sources, gas surroundings, solvents, pH values were investigated to further reveal the reaction process. Graphical abstract: The degradation pathway of refractory nitrobenzene in water through the natural 4-hydroxycoumarin under solar illumination. Highlights: A new natural organic matter could be activated as reducing agent under illumination. 4-hydroxycoumarin as natural compound was found to be an efficient photosensitizer. The refractory nitrobenzene was degraded to 4-aminophenol by 4HC as green process. 4HC excited state (4H-chromene-2, 4-diol radical) as key intermediate was confirmed. Reaction pathway between 4HC and NB was completely proposed by product analysis.